RELATIONSHIP OF ADOLESCENTS BEHAVIOR TO CONSUMPTION OF SOFT DRINKS IN SMPN 5 PEKANBARU YEAR 2016 - - Alhidayati; - Nurhapipa; Rahma Putri (Sistem Informasi, 2017)
Behavior consumption of soft drinks are the actions or deeds regarding how often consume soft drinks per week is calculated. Carbonated drinks consumption habits will have a negative impact when it accumulates in the long term. Have been many studies that explain the negative effects of soft drinks, including carcinogenic benzene in soft drinks is very high, high phosphate content of vital minerals in the body that can trigger heart disease (magnesiumdeficiency), osteoporosis (calcium deficiency) and more. Based on the survey results of the sale of soft drinks in the cafeteria, 5 schools with the highest sales level, is SMP N 5 Pekanbaru selling 6-7 boxes per month. This type of research is quantitative with cross sectional design which was held on 16-18 May 2016 in SMP N 5 Pekanbaru. The population of this research is all student grades 7 and 8 SMP N 5 Pekanbaru which amounted to 541 people, with a sample size of 115 people. Data collected technique by stratified random sampling use questionnaire measuring instrument. Univariate data analysis and use your bivariate chi-square test. The results showed that there was a relationship between the knowledge obtained value (p value = 0.001 value POR = 2.14), Effect of friends (p value = 0.006 value POR = 3.45), Access (p value = 0.029 value POR = 2.70), And advertisement (p value = 0:01 value POR = 3.20) with the consumption of soft drinks. Suggested to the relevant instance, that is SMP N 5 Pekanbaru to provide education and information to as many students on the impact of consuming soft drinks for health when consumed in the long term and excessive, and form healthy canteen, or supervise the beverage products , to minimize the beverage products are bad for health.